F690-F740 is more suitable than F690/F740 for mapping the regeneration of Cd-induced chlorosis in poplar leaves by fluorescence imaging - Solti, Ádám (Acta Biologica Szegediensis, 2008)
The effect of cold treatment on concentration of biogenic amines was compared in the moderately frost-sensitive Triticum aestivum cv. Chinese Spring wheat genotype and in the frost-tolerant Chinese Spring (Cheyenne 5A) and the frost-sensitive Chinese Spring (T. spelta 5A) chromosome 5A substitution lines. To see the dynamics of changes, the plant material was collected after 0d, 1d, 3d, 7d and 21d of treatment at 2°C. Quantitative determination of biogenic amines was accomplished by chromatographic method. The cold treatment caused especially great increase in putrescine and spermidine levels. Chromosome 5A affected the cold induced increase in putrescine content, being larger after 21d of cold treatment in the frost-tolerant Chinese Spring (Cheyenne 5A) compared to the sensitive genotypes, which may indicate the role of putrescine accumulation in frost tolerance.